2011
DOI: 10.4236/scd.2011.13008
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase-positive cells isolated from human hearts have mesenchymal stem cell characteristics

Abstract: Tissue-specific resident cells have been identified as a promising population of progenitor cells for cell-based therapies. We describe here the isolation from adult human hearts of tissue nonspecific alkaline phosphatase-positive cells (ALPL+ cells) with mesenchymal stem cell (MSC) characteristics. Samples from 24 adult cadaveric donors were obtained from a valve bank. Mean total ischemia time was 21.5 ± 9.1 hours. The success rate for the isolation of human heart-derived cells by the explant culture techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
11
1
Order By: Relevance
“…One of the prominent properties of stem cells is their strong ability to exclude Hoechst 33342 dye, which is mediated by ABCG2 protein (Zhou et al, 2001). In fact, it has been reported that ALP (+) cells isolated from the human heart have high ABCG2 activity (de Aguiar et al, 2011). Unfortunately, the present Hoechst 33342 exclusion assay revealed that the ALP (+) HeLa cells were brightly stained, as were the ALP (-) H-1 cells (see Fig.…”
Section: Discussioncontrasting
confidence: 47%
“…One of the prominent properties of stem cells is their strong ability to exclude Hoechst 33342 dye, which is mediated by ABCG2 protein (Zhou et al, 2001). In fact, it has been reported that ALP (+) cells isolated from the human heart have high ABCG2 activity (de Aguiar et al, 2011). Unfortunately, the present Hoechst 33342 exclusion assay revealed that the ALP (+) HeLa cells were brightly stained, as were the ALP (-) H-1 cells (see Fig.…”
Section: Discussioncontrasting
confidence: 47%
“…For example, mesenchymal stem cells (MSCs) could be isolated by selection of ALP-positive cells from human hearts [33]. Present study showed that DFSCs express significantly higher levels of ALP than their counterpart non-stem cells, suggesting that ALP could be a marker for identification and purification of stem cells from dental follicle.…”
Section: Discussionmentioning
confidence: 96%
“…A wide variety of cell types, such as cardiomyocytes, endothelial cells, smooth muscle cells and cardiac resident stromal cells (CRSCs), such as fibroblasts and stem/progenitor cells, are found in the adult heart [1,2]. CRSCs have been isolated and characterized by the ex vivo culture of cardiac explants [3,4,5]. The conditioned media from cultured CRSCs exhibits cardioprotective and regenerative capabilities, being able to drive proliferation, cardiac differentiation and tube formation in endothelial cells [4].…”
Section: Introductionmentioning
confidence: 99%